2015
DOI: 10.1097/sap.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Scaffold-Free Prevascularized Constructs Promote Tissue Repair

Abstract: To evaluate the anastomotic potential of prevascular tissue constructs generated from scaffold-free self-assembly of human endothelial and fibroblast cells, tissue constructs were implanted into athymic mice and immune-competent rats. Analysis of xenografts placed into hind limb muscle defects showed vascular anastomotic activity by 3 days following implantation and persisting for 2 weeks. Integration of the implanted prevascular tissue constructs with the host circulatory system was evident from presence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Satellite cells can be reliably identified by paired box transcription factor Pax-7 which is expressed in both quiescent and activated stages 46 . Although pre-vascularized tissue engineered constructs have been shown to promote satellite cell activation upon implantation in a mild muscle injury model, the effects of pre-innervation on host satellite cell population are yet to be addressed 47 . Separate studies indicate that various neurotrophic factors like NGF and BDNF play a critical role in modulating satellite cell response within an injured muscle 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite cells can be reliably identified by paired box transcription factor Pax-7 which is expressed in both quiescent and activated stages 46 . Although pre-vascularized tissue engineered constructs have been shown to promote satellite cell activation upon implantation in a mild muscle injury model, the effects of pre-innervation on host satellite cell population are yet to be addressed 47 . Separate studies indicate that various neurotrophic factors like NGF and BDNF play a critical role in modulating satellite cell response within an injured muscle 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate re-vascularization remains one of the major challenges to engineer thick skeletal muscle limiting nutrient exchange and survival of implanted cells 23 . Pre-vascularized constructs comprising of preformed vascular networks have been shown to promote microvasculature, vascular perfusion of the graft and inosculation with host vascular system thereby significantly improving muscle regeneration following VML 23,27,47 . Neurotrophic factors like NGF, BDNF, GDNF, NT-3 have been reported to enhance angiogenesis in different tissues like skin, heart and cartilage through receptor mediated activation or recruitment of proangiogenic precursor cells [53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…SPECs were created as previously described [ 43 45 ]. Specifically, 7.2 × 10 5 NHDFs and 1.8 × 10 5 HAMECs were combined and seeded into nonadherent agarose troughs 9 mm long × 1 mm wide × 1 mm deep.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, these constructs displayed biophysical properties and histological characteristics of vascular networks, and we are here adopting the nomenclature of self-organizing prevascularized endothelial-fibroblast constructs (SPECs). Crucially, we have recently found that SPECs rapidly anastomose with host vasculature within 3 days and promote tissue repair [ 45 ]. In this study, we have combined the two separate, but proven, SPEC and JM2 technologies in a novel configuration to create a prevascularized bioartificial pancreas in order to address a critical need in the treatment of chronic pancreatitis and type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For each study group, three scaffolds were implanted in three individual rats. The size of each sample was determined according to the previously published reports (Czajka, Calder, Yost, & Drake, 2015). After 3 weeks, the rats were sacrificed and the scaffolds were removed.…”
Section: In Vivo Transplantation and Characterizationmentioning
confidence: 99%